Sistem Informasi Periklanan dan Pelelangan Barang Hasil Pertanian (Studi Kasus Dinas Pertanian) - Tiur Gantini; Riska Nurnajah (Maranatha University Press, 2015)
Recently technology developed and applied in our daily activities. Among them is the application of technology on advertising activities. The purpose of this application is to help the farmers to market harvest directly to customers so they can get cheaper price and there's no fraud in the broker's side or cropier's side. The application allows admin to promote Dinas Pertanian's (Agriculture Departments) events, manage users, manage categories, manage ads, report estimation, and allows farmers/entrepreneur to give comments, advertise products, search products, auction products, and pay via paypal. The application is added by time series method to predict the harvest needs in every region. The author used PHP programming language and MySQL database to build the application. The data sources were collected from literature study, internet browsing, and outdoor observation. The application can facilitate the advertising activities to run better and minimize the mistakes.Keywords: Advertising, Dinas Pertanian, PHP Programing, Time series.